Histopathological analysis of CD44 and c-Myc in colorectal cancer - Littlewood, Stephanie (2021)
Colorectal cancer is the second highest cause of cancer deaths in the UK. The transcriptional regulator c-Myc and transmembrane protein CD44 are reported to be associated with cancer stem cells and epithelial to mesenchymal transition, which have both been linked to poor outcomes. A cohort of 1000 colorectal cancer patients was assessed by immunohistochemistry for expression of CD44, c-Myc and tumour stromal content. TMA blocks comprised of luminal, central and advancing edge cores were used to account for tumour heterogeneity. High nuclear c-Myc expression in tumour epithelial cells was associated with poor 5 year survival (p <0.001). Surprisingly, it was also associated with a lack of metastasis and low tumour stage. In contrast to previous studies, membranous CD44 expression was associated with low primary tumour stage (p 0.001) and metastasis (p 0.003). Cytoplasmic CD44 staining was observed to follow two distinctive patterns, perhaps representing different variants. CD44 and c-Myc expression in the stroma were localised to lymphocytes and plasma cells, respectively. Both were associated with positive clinical outcomes, including low primary tumour stage and 5 year survival, consistent with previous studies regarding immune infiltration. Increased tumour stroma content was associated with worse outcomes, consistent with the “mesenchymal” consensus molecular subtype 4. CD44 expression and tumour stroma content were significantly correlated, supporting the role of CD44 in epithelial to mesenchymal transition. This study presented an opportunity to better understand the expression of c-Myc, CD44 and the tumour stromal content in colorectal cancer in a large number of patients.